Nanosized iron- or copper-catalyzed homocoupling of aryl, heteroaryl, benzyl, and alkenyl grignard reagents - Moglie, Yanina Fernanda (2008)
Under very mild reaction conditions, iron or copper nanoparticles efficiently promoted the homocoupling of different Grignard reagents in tetrahydrofuran at room temperature. The nanosized iron or copper particles were generated in situ in a simple and economical way from commercially available FeCl2 or CuCl2, respectively, an excess of lithium powder, and a catalytic amount (5 mol%) of 4,4′-di-tert-butylbiphenyl (DTBB) as electron carrier. The reaction of a series of aryl, heteroaryl, benzyl, and alkenyl Grignard reagents in the presence of a substoichiometric amount of the iron or copper nanoparticles led to the formation of the corresponding homocoupling products in good yield. Copyright © Taylor & Francis Group, LLC.